TiO2-based dye-sensitized solar cells prepared with bixin and norbixin natural dyes: Effect of 2,2 '-bipyridine additive on the current and voltage - Carvalho, I. C.; Barbosa, M. L.; Costa, M. J. S.; Longo, E. [UNESP]; Cavalcante, L. S.; Viana, V. G. F.; Santos, R. S. (Elsevier B.V., 2020)
In this paper, we discovered that the 2,2'-bipyridine (bipy) was able to increase the voltage and short circuit current of dye-sensitized solar cells (DSSCs) prepared using bixin and norbixin natural dyes that are environmentally friendly. Titanium oxide (TiO2) film was deposited on FTO-glass. Morphological analysis revealed that the film was porous and consisted of almost spherical particle with an average size of 35 nm. The photoelectric behavior of the DSSCs was evaluated under polychromatic radiation adjusted to 1.5 AM standard. The analysis revealed that the presence of bipy in the electrolyte significantly increased the open circuit voltage (V-OC) values from 299 to 519 mV for the DSSCs prepared using bixin dye, whereas the V-OC values increased from 293 to 311 mV for the DSSCs prepared using norbixin dye. Also, it was observed that the bipy additive positively influenced the short-circuit current (J(SC)) values of these devices. The simultaneous increase in V-OC and J(SC) rendered this bipyridinic compound a good additive candidate for TiO2 nanoparticles-based DSSC using natural dyes.
Keywords: Bixin; Norbixin; TiO2 nanoparticles-based DSSC; Additive electrolyte